2018
DOI: 10.3390/bios8040108
|View full text |Cite
|
Sign up to set email alerts
|

Metal Oxide Nanoparticle Based Electrochemical Sensor for Total Antioxidant Capacity (TAC) Detection in Wine Samples

Abstract: A single-use electrochemical screen-printed electrode is reported based on biomimetic properties of nanoceria particles (CeNPs). The developed tool showed an easy approach compared to the classical spectrophotometric methods reported in literature in terms of ease of use, cost, portability, and unnecessary secondary reagents. The sensor allowed the detection of the total antioxidant capacity (TAC) in wine samples. The sensor has been optimized and characterized electrochemically and then tested with antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 90 publications
(101 reference statements)
0
20
0
Order By: Relevance
“…The sensor does not require any specific storage conditions (e.g., buffer and low temperature) as opposed to enzymatic biosensors. Furthermore, the CeNP-modified electrode has a broader LR for gallic acid and ascorbic acid [269].…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 98%
See 3 more Smart Citations
“…The sensor does not require any specific storage conditions (e.g., buffer and low temperature) as opposed to enzymatic biosensors. Furthermore, the CeNP-modified electrode has a broader LR for gallic acid and ascorbic acid [269].…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 98%
“…Nanomaterials that do not contain copper could also possess laccase mimicking activity. Many metal-based catalysts have been described recently, including noble metal NPs: gold [266], platinum [267], or oxides such as iron oxide [12,17], cerium(IV) oxide [268,269], manganese oxide [270], etc. Huang and coauthors [264] described a laccase-mimic NZ based on copper ions and adenosine monophosphate (AMP-CuNZ) with a 15-fold higher catalytic activity than that of natural laccase (at the same mass concentration; normalization to the molar concentration of both catalysts for calculating k cat was not reported).…”
Section: Laccase-mimicking Nanozymesmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Tortolini et al have compared the electrochemical properties and sensitivity to gallic acid for 3 types of screen-printed electrodes (SPE) modified with ceria nanoparticles (CeNP) by drop-casting [91], namely (i) electrodes with nanostructured carbon, (ii) with carboxylic acid functionalized multi-walled carbon nanotubes (MWCNT) and (iii) with carboxylic acid functionalized multi-walled carbon nanotubes-Fe 3 O 4 superparamagnetic nanoparticles. The authors found that the voltammetric sensor with carboxylic acid-functionalized multi-walled carbon nanotubes (MWCNT/CeNP/SPE electrode) provides the highest electrochemical area and best sensitivity to gallic acid.…”
Section: Biosensors For the Total Antioxidant Capacity (Tac)mentioning
confidence: 99%